2021
DOI: 10.1175/jas-d-20-0214.1
|View full text |Cite
|
Sign up to set email alerts
|

An Eddy–Zonal Flow Feedback Model for Propagating Annular Modes

Abstract: The variability of the zonal-mean large-scale extratropical circulation is often studied using individual modes obtained from empirical orthogonal function (EOF) analyses. The prevailing reduced-order model of the leading EOF (EOF1) of zonal-mean zonal wind, called the annular mode, consists of an eddy-mean flow interaction mechanism that results in a positive feedback of EOF1 onto itself. However, a few studies have pointed out that under some circumstances in observations and GCMs, strong couplings exist bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…In one setup, the parameter settings, forcing, and dissipation are identical to those in the "Held-Suarez benchmark" (Held & Suarez, 1994) in which an analytical profile approximating a troposphere in unstable radiative-convective equilibrium and an isothermal stratosphere are used in the Newtonian relaxation scheme (with an equinoxial condition). The annular mode in this setup is in the non-propagating regime, similar to Lubis and Hassanzadeh (2021). It is known that this setup's annular mode is overly persistent (compared to the reanalysis), which had been often attributed to a too-strong EOF1-onto-EOF1 positive feedback in past studies (Chen & Plumb, 2009;Hassanzadeh & Kuang, 2019).…”
Section: Idealized Gcm Simulationsmentioning
confidence: 79%
See 4 more Smart Citations
“…In one setup, the parameter settings, forcing, and dissipation are identical to those in the "Held-Suarez benchmark" (Held & Suarez, 1994) in which an analytical profile approximating a troposphere in unstable radiative-convective equilibrium and an isothermal stratosphere are used in the Newtonian relaxation scheme (with an equinoxial condition). The annular mode in this setup is in the non-propagating regime, similar to Lubis and Hassanzadeh (2021). It is known that this setup's annular mode is overly persistent (compared to the reanalysis), which had been often attributed to a too-strong EOF1-onto-EOF1 positive feedback in past studies (Chen & Plumb, 2009;Hassanzadeh & Kuang, 2019).…”
Section: Idealized Gcm Simulationsmentioning
confidence: 79%
“…It is known that this setup's annular mode is overly persistent (compared to the reanalysis), which had been often attributed to a too-strong EOF1-onto-EOF1 positive feedback in past studies (Chen & Plumb, 2009;Hassanzadeh & Kuang, 2019). Recently, Lubis and Hassanzadeh (2021) showed that the too-persistent annular mode in this setup is at least partly (if not entirely) due to the lack of cross-EOF feedbacks.…”
Section: Idealized Gcm Simulationsmentioning
confidence: 99%
See 3 more Smart Citations